Shadow Economies Around the World - Size, Causes, and Consequences - Friedrich Schneider; Dominik Enste (Center for Economic Studies and ifo Institute (CESifo), 1999)
Using various methods (currency demand, physical input (electricity) method, model approach), which are discussed and criticized, estimates of the size of the shadow economy in 76 developing, transition and OECD-countries are presented. The average size of a shadow economy varies from 12 percent of GDP for OECD, to 23 percent for transition and to 39 percent for developing countries. An increasing burden of taxation and social security contributions combined with rising state regulatory activities are the drivin g forces for the increase of the shadow economy especially in OECD-countries. According to some findings, a growing shadow economy has a negative effect on official GDP growth, and a positive impact of corruption on the size of the shadow economy can be found.
Keywords: 330